In Search of Successful Firms in Developing Countries, Their Keys Success Factors, Implemented Strategies : Evidence from South Africa, Egypt, Turkey and Russia - Rakhymzhanova, Aliya (2014)
This study challenges itself by addressing the issue of research ignorance towards firms from developing countries due to pessimistic predictions of scholars that stated the absence of any competitive advantages by these regions. However, with the recent changes in the market and growing number of emerging market firms that are successfully competing on international level added the confidence to conduct this research. For the purpose to prove an opposite point of view this study explores the cases of successful companies from selected developing countries, where main attention is given to key success factors of these firms as well as their strategies in use against competition with global MNCs. Literature review on this topic presented a variety of factors that might be responsible for the success of the firms. Besides that, strategy of implementation entirely depends on two components, such industry globalization pressure and firms assert transferability. The study of first and identification of second allows companies from developing markets to apply the strategies that helps them compete not only locally, but also internationally. Analysis part of this work is built with support of secondary data on the numbers of companies that successfully operate in the markets of South Africa, Egypt, Turkey and Russia, where identification of successful firms was possible by application of some financial indicators (positive sales growth, net income and market capitalization). The findings of analysis clearly indicate that developing countries have their own winners where presence of a variety of key success factors in their business performance found support in this study. Based on Dawar and Frost’s typology, there were few ranges of strategies identified among which dominance took a strategy of contender.